Stress group patterns, focus signalling and sentence intonation in two regional Danish standard languages: Aalborg and Næstved - Grønnum Thorsen, Nina (Annual Report of the Institute of Phonetics University of Copenhagen, 1988)
This paper investigates stress group patterns, prosodic focus signalling and sentence intonation contours in Standard Danish as spoken on a substratum of Northern Jutland (Aalborg) and South Zealand (Næstved) dialect. The major difference between these two regions (and the difference to Standard Copenhagen Danish) is to be found in the way segments and Fo patterns are aligned in the prosodic stress group. Both regions share with Copenhagen the global signalling of sentence intonation contours, as well as a pronounced reluctance to indicate, with prosodic means, in this style of delivery, the pragmatic, contextually invited focus of the utterance.